AN ANALYSIS OF TRANSLATION TECHNIQUES USED IN TRANSLATING CULTURAL CATEGORIES IN BROWN’S ORIGIN INTO INDONESIAN - Sherli Noftariani (Universitas Sarjanawiyata Tamansiswa, 2019)
The objectives of this study are (1) to identify some cultural categories used in the novel entitled Origin by Dan Brown and its Indonesian version and (2) to describe the translation techniques used in translating cultural terms found in the novel entitled Origin by Dan Brown and its Indonesian version. This study used descriptive qualitative method. The data were gathered by document analysis of words, phrase and sentences found in the Origin novel and its Indonesian translation that contain cultural categories. The researcher used some theories by Newmark, Molina and Albir, and Nida and Taber to analyze the data related to the cultural terms and the translation techniques. The results showed that there were 112 data which were divided into five kinds of cultural categories proposed by Newmark theory namely (1) ecology, (2) material culture, (3) social culture, (4) organizations, customs, activities, procedures, concepts and (5) gestures and habits. Meanwhile, there were 16 types of translation techniques found in 222 data in translating those cultural categories. The translation techniques were namely (1) Addition, (2) Adaptation, (3) Amplification, (4) Borrowing, (5) Compensation, (6) Description, (7) Deletion, (8) Discursive Creation, (9) Established Equivalence, (10) Generalization, (11) Literal, (12) Modulation, (13) Particularization, (14) Reduction, (15) Transposition, (16) Variation. In addition, the most dominant translation technique used by the translator was borrowing technique.